Anthropogenic Trace Compounds (ATCs) in aquatic habitats — Research needs on sources, fate, detection and toxicity to ensure timely elimination strategies and risk management - Sabine U. Gerbersdorf; Carla Cimatoribus; Holger Class; Karl-H. Engesser; Steffen Helbich; Henner Hollert; Claudia Lange; Martin Kranert; Jörg Metzger; Wolfgang Nowak; Thomas-Benjamin Seiler; Kristin Steger; et al. (Environment International, 2015)
Anthropogenic Trace Compounds (ATCs) that continuously grow in numbers and concentrations are an emerging issue for water quality in both natural and technical environments. The complex web of exposure pathways as well as the variety in the chemical structure and potency of ATCs represents immense challenges for future research and policy initiatives. This review summarizes current trends and identifies knowledge gaps in innovative, effective monitoring and management strategies while addressing the research questions concerning ATC occurrence, fate, detection and toxicity.We highlight the progressing sensitivity of chemical analytics and the challenges in harmonization of sampling protocols and methods, as well as the need for ATC indicator substances to enable cross-national valid monitoring routine. Secondly, the status quo in ecotoxicology is described to advocate for a better implementation of long-term tests, to address toxicity on community and environmental as well as on human-health levels, and to adapt various test levels and endpoints. Moreover, we discuss potential sources of ATCs and the current removal efficiency of wastewater treatment plants (WWTPs) to indicate the most effective places and elimination strategies. Knowledge gaps in transport and/or detainment of ATCs through their passage in surface waters and groundwaters are further emphasized in relation to their physico-chemical properties, abiotic conditions and biological interactions in order to highlight fundamental research needs. Finally, we demonstrate the importance and remaining challenges of an appropriate ATC risk assessment since this will greatly assist in identifying the most urgent calls for action, in selecting the most promising measures, and in evaluating the success of implemented management strategies. Keywords: Micropollutants, Water, Chemical detection methods, Effect-related bioassays, Elimination strategies, Biofilm-influenced sediment dynamics, Environmental risk assessment